2020
DOI: 10.1186/s12885-020-06912-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of induction chemotherapy combined with concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in nasopharyngeal carcinoma patients: a systematic review and meta-analysis

Abstract: Background Induction chemotherapy (IC) combined with concurrent chemoradiotherapy (CCRT) has been recommended as the first-line therapy for locoregional nasopharyngeal carcinoma (NPC). Due to the different chemotherapeutic drugs used in the IC and CCRT, the results remain controversial. Methods PubMed, EMBASE, Web of Science, and Cochrane Library databases were systematically retrieved to search potentially eligible clinical trials up to Sep 11, 2019. Eligible studies were registered and prospective randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…AFFILIATIONS 1 Sun Yat-sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangdong Key Laboratory of Nasopharyngeal Carcinoma Diagnosis and Therapy, Guangzhou, and Chinese Society of Clinical Oncology, Beijing, People's Republic of China 2 American Society of Clinical Oncology, Alexandria, VA 3 National Cancer Centre Singapore/Duke-NUS Medical School, Singapore 4 Stanford University School of Medicine, Stanford, CA 5 Dana-Farber Cancer Institute, Boston, MA 6 Princess Margaret Cancer Centre/University of Toronto, Toronto, Ontario, Canada 7 Central Alabama Radiation Oncology, Montgomery, AL 8…”
Section: Editor's Notementioning
confidence: 99%
“…AFFILIATIONS 1 Sun Yat-sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangdong Key Laboratory of Nasopharyngeal Carcinoma Diagnosis and Therapy, Guangzhou, and Chinese Society of Clinical Oncology, Beijing, People's Republic of China 2 American Society of Clinical Oncology, Alexandria, VA 3 National Cancer Centre Singapore/Duke-NUS Medical School, Singapore 4 Stanford University School of Medicine, Stanford, CA 5 Dana-Farber Cancer Institute, Boston, MA 6 Princess Margaret Cancer Centre/University of Toronto, Toronto, Ontario, Canada 7 Central Alabama Radiation Oncology, Montgomery, AL 8…”
Section: Editor's Notementioning
confidence: 99%
“…Zhang and his colleagues showed that additional gemcitabine and cisplatin IC significantly improved 3-year failure-free survival (FFS) (85.3% in the IC+CCRT group vs 76.5% in the CCRT group) and overall survival (OS) (94.6% in the IC+CCRT group vs 90.3% in the CCRT group) in patients with LANPC [2] . Our published meta-analysis also indicated the superiority of IC+CCRT compared with CCRT alone (5-year OS hazard ratio [HR] 0.77, 95% CI 0.62-0.94, p = 0.01) [3] .…”
Section: Additional Adjuvant Chemotherapy For Locoregioally Advanced Nasopharyngeal Carcinoma In National Comprehensive Cancer Network Gumentioning
confidence: 58%
“…In the cancer center of our hospital (Wuhan Union Hospital), the most adopted AC is taxane plus platinum-based chemotherapy. Since IC+CCRT has been certificated to be superior to CCRT [3] , we suggest whether IC regimens could also be used as AC regimens in LANPC pa-tients. In a recently published study, LANPC patients received the same IC and AC regimens combined with CCRT.…”
Section: Diseases and Researchmentioning
confidence: 99%
“…In our previous study [20], we found that most prospective randomized clinical trials utilized cisplatin 40 mg/m 2 weekly. In patients treated with 40 mg/m 2 cisplatin based CCRT, the 3-year OS rates ranged from 71% to 92% and the 3-year FFS ranged from 57% to 67% [21][22][23].…”
Section: Weekly 30 Mg/m 2 Versus 40 Mg/m 2 Cisplatinmentioning
confidence: 99%
“…For locoregionally advanced NPC patients, mounts of large-scale prospective clinical trials have demonstrated that induction chemotherapy followed by CCRT is the standard of care [4,6,9,21,[26][27][28][29][30]. In a previously published analysis, seven trials were enrolled, with four trials adopting weekly cisplatin schedule and the other three trials adopting triweekly cisplatin schedule [20]. Additionally, CCRT plus adjuvant chemotherapy could also be a therapeutic strategy for NPC patients [7,31].…”
Section: Toxicitiesmentioning
confidence: 99%